On the System CB1 and a Lattice of the Paraconsistent Calculi - Ciuciura, Janusz (Logic and Logical Philosophy, 2019)
In this paper, we present a calculus of paraconsistent logic. We propose an axiomatisation and a semantics for the calculus, and prove several important meta-theorems. The calculus, denoted as CB1, is an extension of systems PI, C min and B1, and a proper subsystem of Sette’s calculus P1. We also investigate the generalization of CB1 to the hierarchy of related calculi.